THE BREAK–EVEN CHART. - Fill, William L. (The Accounting Review, 1952)
Two needed virtues of any accounting report are simplicity and accuracy. Simplicity is essential in a report to convey to the reader the meaning with the least possible inference or interpolation from his own predetermined notions on the matter involved. The break-even chart is just such a summary report. Its simplicity enhances its ability to communicate the relation of sales less variable and fixed costs at different levels of operation quite forcefully to financial analysts outside the company and to the management group within the company. In such a function its use to convey the information in the master budget is undisputed. In plotting sales as a function of volume on a break-even chart it is assumed that sales equals production which, obviously, is not entirely true because of the accumulation or depletion of inventories. Inventories, though, are usually very small in comparison to total production and, for practical purposes, are ignored in computing sales at various levels of production. Since the break-even chart is based on accounting data and is used as an accounting report, it customarily ignores the cost of the investment used to obtain the production and distribution of a company's output.